Improving Problem Solving Abilities in Mathematics Subjects Using Problem-Based Learning - Suryani, Nani (PEDAGOGIA, 2024)
This research aims to determine the application of the problem-based learning (PBL) model to improve students' problem-solving abilities in Mathematics subjects in class. This research is classroom action research carried out in 2 cycles. The research subjects were students of the class. The research procedure consists of 4 stages in each cycle: planning, implementing actions, observing, and reflecting. The biology learning process uses the problem-based learning (PBL) learning method. The indicator of learning outcomes in this research is an increase in students' ability to solve problems in mathematics subjects. The results of the research showed that students' problem-solving skills increased in each cycle; in cycle II, there were nine people in the 90 - 100 (excellent) range, 16 people in the 80 - 89 (good) range, and seven people in the 80 - 89 (good) range. Value range 70 – 79 (medium). These findings underscore the potential of the PBL model to effectively enhance students' capacity to solve mathematical problems, offering a more engaging and effective learning experience.